The Reception of Paul Tillich in Sino-Christian Theology - Chan, Keith Ka-fu (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2025)
This paper aims to present a more comprehensive picture of the reception of Paul Tillich’s thought in China. Firstly, I will argue that Tillich’s works were initially translated into Chinese by Taiwanese academics, who opened an important door to the Chinese reception of Tillich’s theology. However, a more precise and substantial analysis has been completed by numerous academics in Hong Kong. It should be noted that in the past twenty years, numerous doctoral theses were produced in the Chinese University of Hong Kong - an important contribution to promoting the Chinese reception of Tillich. Secondly, I will argue that the Chinese reception of Tillich’s thought can be classified into three areas: Tillich and Buddhism, Tillich and Confucianism, Tillich and the Chinese/contemporary context. Lastly, I will provide some observations about the weaknesses of the current situation in the Chinese reception of Tillich’s works.